Unidades de insuficiência cardíaca - Timóteo, Ana Teresa (2020)
The prevalence of heart failure has increased over the past decades and is a major social and economic burden on healthcare services. Patient quality of life is severely impaired and heart failure is one of the main causes of death in Portugal. The functional organization of multidisciplinary teams engaged in the treatment of these patients is essential to improve health care provision and outcomes, specifically reducing mortality, hospital admissions, and improving quality of life. We describe current approaches to heart failure management and discuss the organization of heart failure units and cooperation among these units and also with other healthcare professionals.